2004
DOI: 10.1007/s00467-004-1539-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening for vesicoureteral reflux and renal scars in siblings of children with known reflux

Abstract: The incidence of vesicoureteral reflux (VUR) in the general population is less than 1%, but it is high in families with reflux. The reported prevalence of VUR among siblings of index patients with reflux has ranged from 4.7% to 51%. Reflux carries an increased risk of pyelonephritis and long-term renal impairment. The purpose of this study was to identify the age-related incidence and severity of reflux, and the frequency of associated renal parenchymal damage in siblings of children with reflux in order to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 61 publications
2
20
0
1
Order By: Relevance
“…We have found that reflux severity in these asymptomatic children varies widely from mild to severe (68)(69)(70). The incidence of renal cortical damage in these siblings with VUR is high (68,(71)(72)(73)(74).…”
Section: Vesicoureteral Reflux (Vur)mentioning
confidence: 83%
“…We have found that reflux severity in these asymptomatic children varies widely from mild to severe (68)(69)(70). The incidence of renal cortical damage in these siblings with VUR is high (68,(71)(72)(73)(74).…”
Section: Vesicoureteral Reflux (Vur)mentioning
confidence: 83%
“…The incidence of VUR in siblings in previous studies was reported as 27% by Wan et al (17) and 51% by Parekh et al (18). Hollowel and Greenfield (19) have found the incidence of VUR in siblings as 32% in their study and the incidence was found 42.5% by Ataei et al (20).…”
Section: Discussionmentioning
confidence: 86%
“…5,6 But in some recent studies from America and Europe showed that the incidence was much higher and it was 17-70% in children with UTI. [2][3][4]7 On the other hand the incidence is much lower(7%) in west African descendents. 8 There are no controversy regarding association of VUR, UTI and renal scarring.…”
Section: Introductionmentioning
confidence: 99%